Sistem Perilaku Anak Pengguna Gadget Di Desa Legoksari Kecamatan Tlogomulyo Kabupaten Temanggung - Lestari, Asmawati Eka (Jurnal Publisitas, 2020)
The development of technology and information in the global world continues to increase. Expansion of the results of technological and information development in the form of gadget communication tools and an internal set not only entering urban communities but rural communities, so that they have a direct impact both positive and negative aspects that can be easily accessed by people who slowly change people's thinking and lifestyle rural. Lack of preparedness of parents in facing the challenges of technological and information development provides changes in the development of children's behavior when children use gadgets. This study aims to determine the behavior of children of gadget users in Legoksari Village, Tlogomulyo District, Temanggung Regency. This research method uses a qualitative descriptive approach to describe the results of data obtained from the field. Data collection uses interviews and observation.The results of this study are 1) Family sub system: The characteristics of parenting in implementing discipline will shape the awareness behavior of children in using gadgets. 2) Peer Sub System: children who have strong interactions with peer groups who use gadgets, will lead to the habit of using gadgets and will experiment with the results of interactions in peers. 3) Sub-system of cultural environment: Changes in the behavior of children using gadgets occur because of changes in the cultural environment that is increasingly consumptive to the development of technology and information.